Reflexo do compartilhamento de informações entre os fiscos na arrecadação do ITCMD no Estado do Ceará - Couto, Amarildo Antônio do (2016)
The States Departments of Taxation and Finance have signed and updated mutual cooperation agreements with the Tax Authorities to cross data and facilitate the tax inspection. The expected result of the measure is an increase in tax collection as ICMS, property taxes and the Cause Transfer Tax Inheritance and Donations (ITCMD). Since 2007 the Secretariat of the Ceará State Finance started the operation of the agreement with the Internal Revenue Service of Brazil for the exchange of information from the tax returns of individuals (DIRPF) enabling the identification of taxpayers who did or received donations and did not collect the ITCMD. The impact on revenues from the information exchange measures DIRPF domiciled taxpayers in the State of Ceará was analyzed in this work, using econometric methodology of the difference estimator in differences in a database the years 2003-2013 and the 2007, when it was started the exchange of information, such as timeframe for a comparison of the before and the after. To check the currency effect on the impact of the collection, it was necessary to measure the amounts collected in the period from 2003 to 2013 in constant currency. We measured the amounts collected to 2013 prices using the IPCA (National Index of Consumer Price). As a result there was no significant increase in revenue. However, the number of contributors has nearly tripled in the period.